Conhecimento, sociabilidade e lazer em jogos online : uma etnografia na "Lan House do Paulo" em São Gonçalo do Amarante-RN - Silva, Emerson Henrique da (2012)
In a highly dynamic society such as we live, have access to the virtual world is an increasingly common practice, is aiming to study, work or to search leisure through chat rooms, sites and games, being incorporated by the most varied groups that end up appropriating these new possibilities of interaction, shaping them in order to adapt them to their needs / wants. The specific purposes pursued through the use of tools available over the Internet can vary considerably when one takes into account specific user groups, which makes the topic quite relevant to problematization, especially when we take into account access through lan houses. This research seeks to study the networks of knowledge, sociability and leisure formed by young people who frequented the "Lan house do Paulo" in São Gonçalo do Amarante - RN based on the use of the online role-playing-game World of Warcraft, which makes possible the interaction of several users through an avatar resident in a virtual world, theoretically questioning the importance of this type of platform for the development and maintenance of social interactions among its users